THE EFFECT OF WORK STRESS AND DISCIPLINE ON EMPLOYEE PERFORMANCE AT CAPELLA MULTIDANA COMPANY MEDAN - Diana Sari Harahap; Soulthan Saladin Batubara; Ali Amran (CERED Indonesia Institute, 2020)
Improved employee performance has become very important considering the increasingl currents of globalization where competition is getting stronger as knowledge and technology advances. This change brought implications for the professionalism of the employees in answering the demands of competition in the face of the globalization flow. Thus employee performance increase is absolutely necessary as well as the the ability of the organization to control the employee’s stress level,discipline and the promotion of position in the organization as well in order to fulfill the achievement of performance objectives optimally so that the company can survive and win the competition. This research aims to know and analyse the influence of work stress and discipline on the performance of employees at Capella Multidana Company Medan. With the Simple Random Sampling technique and using the Slovin formula with 5% percentage of looseness (e), then obtained samples in this study a number of 104 employees who are the status of permanent officers. Data is collected through questionnaire, interviews and documentation studies. The poll is calculated by the measurement unit of Likert scale, and processed using SPSS (statistical product and service solution) program. The results showed that simultaneously, work stress and discipline were positively and significantly impacted the employee performance. Partially, discipline were positively and significantly impacted the employee performance but work stress were negatively impacted the employee performance of Capella Multidana Company Medan.